Academic Supervision By The Head of Madrasah To Improve The Performance of Educators - Jannah, Roudlotul; Zakariyah, Zakariyah; Zamroni, M Afif (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
. The focus of this research is as follows; 1) How is the planning of the headmaster’s academic supervision program to improve the performance of educators at MIS Raden Rahmat Balongbendo Sidoarjo? 2) What is the strategy for implementing the headmaster’s academic supervision program to improve the performance of educators at MIS Raden Rahmat Balongbendo Sidoarjo? 3) How is the supervision of the implementation of the headmaster’s academic supervision program to improve the performance of educators at MIS Raden Rahmat Balongbendo Sidoarjo? 4) How to evaluate the implementation of the headmaster’s academic supervision program to improve the performance of educators at MIS Raden Rahmat Balongbendo Sidoarjo? 5) What is the follow-up plan for the academic supervision of the headmaster to improve the performance of educators at MIS Raden Rahmat Balongbendo Sidoarjo? The type of research used in this research is descriptive with a qualitative approach. This type of descriptive research accommodates all qualitative data information according to different descriptions, not only presenting numerical statements or results in the form of numbers. The approach used in this research is a case study to look carefully for events, activities, processes, and cases limited by time, so that various procedures are used according to a predetermined time.The results of this study are, 1) At the planning stage of the academic supervision program at MIS Raden Rahmat Balongbendo, the head of the madrasa emphasizes identifying the problems faced by educators as well as SWOT analysis to determine strengths, weaknesses, opportunities and threats in the aspects of the learning activities they carry out , 2) the head of the MIS Raden Rahmat Balongbendo madrasa in carrying out the academic supervision program using supervision approaches, techniques and instruments that had been prepared beforehand, 3) The head of the MIS madrasa Raden Rahmat Balongbendo supervised the implementation of academic supervision related to the progress of educators in carrying out the instructions of the head of the madrasa as a supervisor not only looking for teacher mistakes, but also looking for positive things done by educators, for further development, 4) the head of the MIS madrasa Raden Rahmat Balongbendo evaluates academic supervision to find out the success of the strategy for implementing the academic supervision program, 5) the headmaster of the MIS Raden Rahmat Balongbendo carries out follow-up on the academic supervision of the madrasah head to improve the performance of educators in accordance with the results of the evaluation of the academic supervision that has been carried out.